The effect of gentiopicroside on brain tissue repair in mice during the acute phase of middle cerebral artery occlusion - Ling Kui; Guoyun Wang; Li Zhang; Qifeng Liao; Xi Li; Shuangshuang Wang; Tao Chen; Bingfeng Leng; Jinqun Huang; Yinming Jiao; Qiaoyuan Ye; Qingqian Zeng; et al. (Molecular Biology Reports, 2026)

Mechanism-driven nanostrategies against intracellular infections: Leveraging the host-pathogen interplay - Junheng Zhu; Bingfeng Wu; Meng Luo; Yangqing Peng; Fan Yang; Liu Liu; Zhenming Wang; Dingming Huang (Chemical Engineering Journal, 2026)

Storage–supply regulation and rainfall responses driven by thermokarst lakes in permafrost-degrading catchments - Junhao Cui; Jia Qin; YongJian Ding; Yongyong Zhang; Bingfeng Yang; Feiteng Wang; Xiaobo He; Guangxi Ding (Journal of Hydrology, 2026)

Fragment-based diffusion modeling and molecular dynamics simulation validation for the discovery of PD-L1 small-molecule inhibitors - Jun Liu; Yuxing Yi; Xiaoyan Wu; Jianhuai Liang; Boping Liu; Bingfeng Wang (Molecular Diversity, 2026)

Corrugated aerogel with directional channels for enhanced oil adsorption and emulsion purification - Yuan Wang; Dafan Chen; Bingfeng Li; Wenjun Zhang; Yiming Li (Journal of Hazardous Materials, 2026)

Analysis of micromix combustion characteristics of hydrogen doped with CH4 or NH3 in a water-cooled tubular environment - Ning Wang; Shifeng Deng; Teng Qu; Yifan Du; Bingfeng Zhou; Wenyu Dou; Di Tian; Qinxin Zhao (Fuel, 2026)

Structural heterogeneity and anisotropy beneath Myanmar: Insights into the complex deformation of the Indo-Burma subduction zone - Yiming Bai; Shengji Wei; Jing Chen; Tianjue Li; Bingfeng Zhang; Xiao Xiao; Shucheng Wu; Jiayuan Yao; Yu Wang; Ping Tong (Earth and Planetary Science Letters, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Experimental and numerical investigation of hydrogen jet diffusion and micromix combustion between water-cooled tube bundles - Ning Wang; Yifan Du; Bingfeng Zhou; Teng Qu; Wenyu Dou; Qinxin Zhao; Di Tian; Shifeng Deng (Fuel, 2026)

Sub-metre surface water mapping using Sentinel-1/2 with integrated super-resolution and deep learning - Jie Song; Jinyan Tian; Lin Zhu; Bingfeng Zhou; Xinyuan Qu; Che Wang; Niu Luo; Zhenxin Zhang; Lin Guo; Mingliang Gao; Xiaojuan Li; Huili Gong (International Journal of Remote Sensing, 2025)

Biodegradable hierarchical hydrogel cellulose membrane for viscous crude oil/water emulsion separation: Performance and mechanistic insights - Dafan Chen; Shideng Yuan; Bingfeng Li; Mutai Bao; Wenjun Zhang; Zhining Wang; Yiming Li (Chemical Engineering Journal, 2025)

Lifetime probabilities of developing and dying from cancer in China: comparison with Japan and the United States in 2022 - Qian Zhu; Yifei Yao; Ru Chen; Bingfeng Han; Shaoming Wang; Li Li; Kexin Sun; Rongshou Zheng; Wenqiang Wei (Science China Life Sciences, 2025)

Ultrasound-enhanced dual-responsive bismuth nanocatalysts for alleviating tumor hypoxia and promoting breast cancer sonodynamic-immunotherapy - Junjie Pan; Huihui Qian; Jiajia Zheng; Xueyu Li; Bingfeng Wang; Jun Du; Liping Gu; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2025)

EIS equivalent circuit modeling of direct ammoniafuel cell (DAFC) and mass transfer characteristics for anode diffusion layers with different hydrophobicity - Yanchen Lai; Bowen Wang; Bingfeng Zu; Chasen Tongsh; Zhengguo Qin; Qing Du; Shangfeng Jiang; Kui Jiao (Chemical Engineering Journal, 2025)

GLP-1 signaling-regulated SNAP25 is involved in improved insulin secretion in diabetic GK rats after Roux-en-Y gastric bypass surgery - Xiangchen Kong; Chao Lin; Chenxi Yang; Xin Wang; Bingfeng Li; Dan Yan; Yanhui Yang; Anyi Hu; Yanyin Chen; Xiaohui Xu; Xiaosong Ma (Molecular Biology Reports, 2024)

Prominent creep characteristics of thermokarst landslides on central Tibetan Plateau under climate warming conditions - Ya Liu; Haijun Qiu; Jiading Wang; Ninglian Wang; Xingyuan Jiang; Bingzhe Tang; Dongdong Yang; Bingfeng Ye; Ulrich Kamp (CATENA, 2024)

Integrating Anthropogenic–Pesticide Interactions Into a Soil Health‐Microbial Index for Sustainable Agriculture at Global Scale - Nuohan Xu; Bingfeng Chen; Yan Wang; Chaotang Lei; Zhenyan Zhang; Yangqing Ye; Mingkang Jin; Qi Zhang; Tao Lu; Huaping Dong; Jianxin Shou; Josep Penuelas; et al. (Global Change Biology, 2024)
Soil microbiota in intensive agriculture are threatened by pesticides, economic activities, and land‐use changes. However, the interactions among these anthropogenic factors remain underexplored. By analyzing 2356 soil metagenomes from around the world, we developed a comprehensive soil health‐microbial index that integrates microbial diversity, nutrient cycling potential, metabolic potential, primary productivity, and health risks to assess how the soil microbiota respond to anthropogenic factors. Our results indicated that the health‐microbial index was the lowest with severe pesticide contamination. Pesticides, in combination with other anthropogenic and climatic factors, exacerbate the decline in this index. Machine learning predictions suggest that the health‐microbial index in approximately 26% of global farmland could decline between 2015 and 2040, even under sustainable development scenarios. Even with strategies to reduce pesticide usage, we cannot completely halt the decline in the health‐microbial index. Our findings highlight that sustaining soil microbial health on a global scale requires addressing not only pesticide management but also broader anthropogenic impacts.

Photocatalytic degradation of organophosphorus flame retardants in aqueous solutions: a review and future prospects - Zihui Xu; Lucheng Zhang; Tingting Wang; Mingqing Zhang; Gang Kang; Shilong Wu; Bingfeng Liu (Environmental Science and Pollution Research, 2024)

Molecular design of hydroxamic acid-based derivatives as urease inhibitors of Helicobacter pylori - Na Wang; Xiaoyan Wu; Jianhuai Liang; Boping Liu; Bingfeng Wang (Molecular Diversity, 2024)

Retraction Note: Evaluating an economic application of renewable generated hydrogen: A way forward for green economic performance and policy measures - Baijun Wu; Bingfeng Zhai; Huaizi Mu; Xin Peng; Chao Wang; Ataul Karim Patwary (Environmental Science and Pollution Research, 2024)

Effects of different assembly strategies on gene annotation in activated sludge - Meng Liu; Nuohan Xu; Bingfeng Chen; Zhenyan Zhang; Xinyu Chen; Yuke Zhu; Wenjie Hong; Tingzhang Wang; Qi Zhang; Yangqing Ye; Tao Lu; Haifeng Qian (Environmental Research, 2024)

Synergistic degradation of Tris (2-Chloroethyl) Phosphate (TCEP) by US/Fenton system: Experimental, DFT calculation and toxicity evaluation - Lucheng Zhang; Tingting Wang; Mingqing Zhang; Qi Liu; Yi She; Shilong Wu; BingFeng Liu (Environmental Science and Pollution Research, 2024)

Phages in different habitats and their ability to carry antibiotic resistance genes - Yan Wang; Zhenyan Zhang; Jian Kang; Bingfeng Chen; Wenjie Hong; Binghai Lv; Tingzhang Wang; Haifeng Qian (Journal of Hazardous Materials, 2024)

Sequential recovery of protein and ammonium from waste sludge and functional metabolism in a combined process of nutrient recovery electro-fermentation (NREF) - Jiayu Gu; Huihui Zhou; Jing Wang; Kun Feng; Guojun Xie; Bingfeng Liu; Defeng Xing (Resources, Conservation and Recycling, 2024)

Synthesis, characterization and performance evaluation of a nontoxic functional plasticizer for poly(vinyl chloride) derived from sustainable lactic acid - Bingfeng Qian; Panpan Peng; Chenliang Wang; Lijie Wang; Jianan Zhang; Mingyuan Wu; Jiuyi Liu; Qingyun Wu; Jianjun Yang (Journal of Cleaner Production, 2024)

Pollution characteristics and potential health effects of airborne microplastics and culturable microorganisms during urban haze in Harbin, China - Jiahui Jiang; Hongyu Ren; Xiaowei Wang; Bingfeng Liu (Bioresource Technology, 2024)

Metagenomic analysis of antibiotic-resistance genes and viruses released from glaciers into downstream habitats - Yan Wang; Nuohan Xu; Bingfeng Chen; Zhenyan Zhang; Chaotang Lei; Qi Zhang; Yanpeng Gu; Tingzhang Wang; Meixia Wang; Josep Penuelas; Haifeng Qian (Science of The Total Environment, 2024)

Synthesis, characterization and performance evaluation of a flame retardant plasticizer for poly(vinyl chloride) derived from biobased vanillic acid - Bingfeng Qian; Weiyao Wang; Huichao Zhu; Jianan Zhang; Mingyuan Wu; Jiuyi Liu; Qingyun Wu; Jianjun Yang (Chemical Engineering Journal, 2023)

A global atlas of marine antibiotic resistance genes and their expression - Nuohan Xu; Danyan Qiu; Zhenyan Zhang; Yan Wang; Bingfeng Chen; Qi Zhang; Tingzhang Wang; Wenjie Hong; Ning-Yi Zhou; Josep Penuelas; Michael Gillings; Yong-Guan Zhu; et al. (Water Research, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Global distribution of marine microplastics and potential for biodegradation - Bingfeng Chen; Zhenyan Zhang; Tingzhang Wang; Hang Hu; Guoyan Qin; Tao Lu; Wenjie Hong; Jun Hu; Josep Penuelas; Haifeng Qian (Journal of Hazardous Materials, 2023)

Accelerating drug repurposing for COVID-19 treatment by modeling mechanisms of action using cell image features and machine learning - Lu Han; Guangcun Shan; Bingfeng Chu; Hongyu Wang; Zhongjian Wang; Shengqiao Gao; Wenxia Zhou (Cognitive Neurodynamics, 2023)

Metatranscriptome deciphers the effects of non-antibiotic antimicrobial agents on antibiotic resistance and virulence factors in freshwater microcosms - Yan Wang; Kepin Ni; Zhenyan Zhang; Nuohan Xu; Chaotang Lei; Bingfeng Chen; Qi Zhang; Liwei Sun; Yiling Chen; Tao Lu; Haifeng Qian (Aquatic Toxicology, 2023)

Boosting the performance and durability of heterogeneous electrodes for solid oxide electrochemical cells utilizing a data-driven powder-to-power framework - Yang Wang; Chengru Wu; Siyuan Zhao; Zengjia Guo; Minfang Han; Tianshou Zhao; Bingfeng Zu; Qing Du; Meng Ni; Kui Jiao (Science Bulletin, 2023)

Metagenomic reveals the methanogenesis metabolic mechanism of high-solids anaerobic digestion of human feces under gradient domestication - Haipeng Wang; Hao Sun; Hongyu Ren; Guangli Cao; Guojun Xie; Defeng Xing; Nanqi Ren; Bingfeng Liu (Chemical Engineering Journal, 2023)

Thermophilic dark fermentation fast start-up of hydrogen production with substrate concentration regulation and moderate pretreatment inoculum - Tianming Yin; Wei Wang; Shengnan Zhuo; Guangli Cao; Hongyu Ren; Jianrui Li; Defeng Xing; Guojun Xie; Bingfeng Liu (Fuel, 2023)

RETRACTED ARTICLE: Evaluating an economic application of renewable generated hydrogen: A way forward for green economic performance and policy measures - Baijun Wu; Bingfeng Zhai; Huaizi Mu; Xin Peng; Chao Wang; Ataul Karim Patwary (Environmental Science and Pollution Research, 2022)

Multi-GNSS precise point positioning (MGPPP) using raw observations - Teng Liu; Yunbin Yuan; Baocheng Zhang; Ningbo Wang; Bingfeng Tan; Yongchang Chen (Journal of Geodesy, 2017)

Determination of differential code biases with multi-GNSS observations - Ningbo Wang; Yunbin Yuan; Zishen Li; Oliver Montenbruck; Bingfeng Tan (Journal of Geodesy, 2016)

Replication of Chinese sacbrood virus in primary cell cultures of Asian honeybee (Apis cerana) - Xiaocui Xia; Qianzhou Mao; Haitao Wang; Bingfeng Zhou; Taiyun Wei (Archives of Virology, 2014)

Sensitivity analyses of different vegetations responding to climate change in inland river basin of China - Peng Hou; Qiao Wang; Guangzhen Cao; Changzuo Wang; Zhiming Zhan; Bingfeng Yang (Journal of Geographical Sciences, 2012)

Chemical composition of fennel essential oil and its impact on Staphylococcus aureus exotoxin production - Jiazhang Qiu; Hongen Li; Hongwei Su; Jing Dong; Mingjing Luo; Jianfeng Wang; Bingfeng Leng; Yanhong Deng; Juxiong Liu; Xuming Deng (World Journal of Microbiology and Biotechnology, 2012)